Occurrence of Fungi in Pond Water (Dumaratarai Talab) of Raipur City, C.G., India - Saju*, Deo Sajal (Journal of Phytology, 2011)
Raipur is the capital town of the newly formed state of Chhattisgarh. Various types of spore producing fungi are present in pond water. During the period of present investigation overall total 91 fungal species (362 colonies) belonging to 45 fungal genera are isolated from Dumaratarai Talab ponds of Raipur city. Maximum numbers of fungal species are isolated during winter season, moderate in rainy season and minimum is summer season. Maximum (32 fungal species) numbers of fungal species are isolated in December month and minimum (05 fungal species) in March. All these fungi are highly adaptable to this pond water environment.